2021
DOI: 10.3389/fimmu.2021.597761
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Immunoregulatory Networks in Severe Drug Hypersensitivity

Abstract: The immunomodulatory effects of regulatory T cells (Tregs) and co-signaling receptors have gained much attention, as they help balance immunogenic and immunotolerant responses that may be disrupted in autoimmune and infectious diseases. Drug hypersensitivity has a myriad of manifestations, which ranges from the mild maculopapular exanthema to the severe Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and drug reaction with eosinophilia and systemic symptoms/drug-induced hypersensitivity syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 238 publications
(274 reference statements)
0
15
0
1
Order By: Relevance
“…Insufficient regulation by regulatory T cells (Tregs) may play a role in severe hypersensitivity reactions. Immune checkpoint inhibitors (anti-CTLA-4 and anti-PD-1) in cancer treatment may also induce SJS/TEN and DRESS/DIHS and other hypersensitivity reactions [201].…”
Section: Immunopharmacogenomics and Cutaneous Adrsmentioning
confidence: 99%
“…Insufficient regulation by regulatory T cells (Tregs) may play a role in severe hypersensitivity reactions. Immune checkpoint inhibitors (anti-CTLA-4 and anti-PD-1) in cancer treatment may also induce SJS/TEN and DRESS/DIHS and other hypersensitivity reactions [201].…”
Section: Immunopharmacogenomics and Cutaneous Adrsmentioning
confidence: 99%
“…The drug triggering SJS binds the T cell receptor and MHC class I, and as a result, it leads to the massive replication of cytotoxic T cells, which directly kill keratinocytes, and the release of granulysin, which destroys cells in the skin and the mucous membrane[ 20 ]. Yun-Shiuan’s research showed that the blockade of PD-1/PD-L1 may contribute to the imbalance of the immune system, manifesting the enhancement of the T cell response and increasing the incidence of hypersensitivity[ 21 ]. During the treatment of SJS induced by ipilimumab and nivolumab in a melanoma patient[ 22 ], an increase in CD8+ T cells in the dermal epidermal junction and an increase in PD-L1 expression in keratinocytes were noted.…”
Section: Discussionmentioning
confidence: 99%
“…The field of immune checkpoint inhibition represents an exciting prospect for targeted enhancement of T-cell antigenicity, particularly in cancer therapy [55], whereas dysregulation of this system may impact on susceptibility to drug hypersensitivity. This is because the same mechanism that is known to enhance tumorigenic T-cell activity, unfortunately may result in uncontrolled T-cell activation leading to a barrage of autoimmune and drug hypersensitivity events [56,57 ▪▪ ]. One such drug example is with the radio contrast media amidotrizoate, where a patient received multiple doses without issue; however, concomitant administration of the PD-L1 blocker atezolizumab resulted in severe hypersensitivity manifestations [57 ▪▪ ].…”
Section: Signal 2 and Immune Dysregulationmentioning
confidence: 99%